Pembentukan Pribadi Kreatif Dan Semangat Belajar Anak Di Panti Asuhan Rapha-El - Bengkel; Geopani Pakpahan (Yayasan Literasi Sains Indonesia, 2022)
Creativity is something that is usually needed by someone in doing a job, including producing work. Creativity is also the skill of determining new ideas by looking at the subject from a new perspective and forming new combinations of two or more concepts in mind. Many children do not understand what creativity is, especially the children of the Rapha-El orphanage. Since the pandemic period, the process of teaching and learning activities in schools is very limited, namely only through online so that students often find it difficult to develop talent and creativity. carried out with the casework method through a general intervention stage consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The focus of the client problem solving process is the use of fun and unique learning for the formation of the client's creative personality. It is hoped that after doing the practicum at the Rapha-El orphanage, the children are expected to be able to understand and understand that creativity is important in life, especially in early childhood because it can make people more productive.